(No) Exit from liberalism?. Issue 3 (September 2020) - Cooley, Alexander; Nexon, Daniel H
Post-Cold War expansion of liberal order rested on three legs: the implosion of major alternative ordering projects, the enjoyment by liberal democracies of a "patronage monopoly, " and the dominance of liberalizing transitional activist networks and movements. By 2019, all three of those legs have been turned upside down. China and Russia, among others, offer new ordering projects, countries enjoy "exit options" in the form of alternative patronage, and illiberal activist networks are in the ascendant. A closer look at the "why" and "how" makes clear that illiberal forces have appropriated and repurposed the toolkit used to expand liberal order, which suggests an apparent paradox. While some forms of liberal order—primarily on the political side—are in retreat, other forms of liberal order—especially in terms of institutional and multilateral arrangements—are being reinforced. We are, therefore, looking not at the end of liberal order, but at a third great transformation in it.